2015
DOI: 10.14814/phy2.12648
|View full text |Cite
|
Sign up to set email alerts
|

Muscle damage and inflammation after eccentric exercise: can the repeated bout effect be removed?

Abstract: The current consensus in exercise physiology is that the repeated bout effect always appears after few eccentric exercise sessions. This is the first attempt to challenge this tenet, by exploiting specificity in muscle plasticity. More specifically, we examined whether the opposing adaptations in muscle induced after concentric and eccentric exercise can attenuate and/or remove the repeated bout effect. Seventeen young men were randomly assigned into one of the following groups: (1) the alternating eccentric‐c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 38 publications
3
36
0
Order By: Relevance
“…Similar results from two cross-over investigations examining BCAA supplementation on recovery of muscle function in untrained individuals reported favorable outcomes of muscle function assessments [ 39 , 40 ]. However, these findings may be influenced by the repeated bout phenomena and should be considered a limitation [ 41 , 42 ]. While MVIC testing is a popular, valid and reliable measure of muscle function and recovery [ 43 ], it is important to note that the isometric movement associated with MVIC testing is distinctly different from several types of athletic performance movements.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results from two cross-over investigations examining BCAA supplementation on recovery of muscle function in untrained individuals reported favorable outcomes of muscle function assessments [ 39 , 40 ]. However, these findings may be influenced by the repeated bout phenomena and should be considered a limitation [ 41 , 42 ]. While MVIC testing is a popular, valid and reliable measure of muscle function and recovery [ 43 ], it is important to note that the isometric movement associated with MVIC testing is distinctly different from several types of athletic performance movements.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has to be taken into account that the protocol adopted in the current study is, to our knowledge, the first one able to elicit eccentric contractions of the jaw‐closing muscles, but still in association with concentric contractions. Even though it has been proved in limb studies that also not‐eccentric‐only exercises can still play a protective role on muscle damage, a recent study showed that alternating cycles of eccentric‐only and concentric‐only contractions reduced dramatically the positive effects by reversing muscles back to their unaccustomed status . Therefore, it can be hypothesised that being able to perform eccentric‐only contractions of the masticatory muscles might produce greater protective effects against muscle damage.…”
Section: Discussionmentioning
confidence: 99%
“…Even though it has been proved in limb studies that also not-eccentric-only exercises can still play a protective role on muscle damage, 15 a recent study showed that alternating cycles of eccentric-only and concentric-only contractions reduced dramatically the positive effects by reversing muscles back to their unaccustomed status. 30 Therefore, it can be hypothesised that being able to perform eccentric-only contractions of the masticatory muscles might produce greater protective effects against muscle damage. However, due to the muscle anatomy and physiology of the craniofacial complex, eccentric-only contractions are unlikely to be developed in human jaw muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigators have shown that prior muscle action history influences subsequent physiological responses to eccentric loading (McHugh et al, 1999 ; Nosaka et al, 2001 ; Margaritelis et al, 2015 ). Adaptations involving the skeletal muscle ultrastructure and the ability to withstand oxidative stress may occur in response to submaximal eccentric loading (Lima and Denadai, 2015 ; Deyhle et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%